Numerical Analysis of Conjugate Heat Transfer of Supercritical CO2 and Pb‐Bi in Tube‐in‐Tube Channels. Issue 3 (5th September 2022) - Ali, Kashif; Qaisrani, Mumtaz A.; Rehman, Haseeb Ur; Ali, Hafiz Muhammad; Rehman, Zia Ur; Baluch, Mansoor A.
Abstract: This work presents a numerical analysis of conjugate heat transfer in an annular channel with turbulence models for supercritical CO2 (tube side) and Pb‐Bi (annular side) as working fluids to understand the impact of flow constraints and heat transfer. By using the Navier‐Stokes formulation and the energy equation clarifying concurrent flow buildup and conjugate heat transmittance in tubes, several turbulent Prandtl models were solved numerically. The turbulent Prandtl number Pr t of Pb‐Bi was used to refine the consistency of the arithmetical simulation. By comparing Pr t, temperature fluctuation, and heat flux density, it was concluded that the existing Pr t model should be used with caution in the numerical calculation of liquid metals having low Pr . The heat transfer and flow phenomena at different Pr t values are significantly different. Abstract : Supercritical carbon dioxide (SCO2 ) can be used to achieve higher thermal efficiency, e.g., in the Brayton power cycle, and liquid metals such as Pb‐Bi are widely used in energy systems, e.g., as coolants. Conjugate heat transfer in an annular channel with turbulence models for SCO2 and Pb‐Bi as working fluids was analyzed numerically to understand the impact of flow constraints and heat transfer.